Attrition and Rape Case Characteristics: A Profile and Comparison of Female Sex Workers and Non-Sex Workers. (July 2016) - Lea, Susan J.; Callaghan, Lynne; Grafton, Iain; Falcone, M. Aurora; Shaw, Steve
The attrition of rape cases from the criminal justice system (CJS) remains high and there is a paucity of research in relation to marginalized groups. Sex workers (SWs) are vulnerable to sexual violence due to the nature of their work. They are also unlikely to report such violence to police for a range of reasons. Two stages of research sought to describe the victim, perpetrator, and offense characteristics of SW rape and to examine the attrition of these cases. All rapes and attempted rapes ( N = 1, 146) reported to police in a large city in the South West of England over a 21-year period were examined; 67 cases involved SWs. Data were extracted from police files in line with the variables of interest. Secondary analysis of the total number of SW rapes ( n = 67) resulted in a profile of these cases. A matched pairs study revealed significant differences in victim, perpetrator, and assault characteristics between SW ( n = 62) and non-sex-worker (NSW) samples ( n = 62). Although no significant difference was found in terms of attrition from the CJS, SW cases were observed to secure more convictions for rape than NSW cases. The implications of the findings for practice and future research are discussed.